2018
DOI: 10.1080/0142159x.2018.1465180
|View full text |Cite
|
Sign up to set email alerts
|

Interprofessional learning experiences: Exploring the perception and attitudes of Saudi Arabian medical and dental students

Abstract: There is an overall positive response towards IPL and the value of team work; however, more attention needs to be paid to enabling students to learn about the specific roles of each profession in the healthcare team.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 22 publications
4
16
0
1
Order By: Relevance
“…Similar results were obtained in previous studies as well [4][5][6][7][8][9][11][12][13][14][15][16][17][18]. Accordingly, there were differences among students' attitudes based on their study profile both in our study and studies conducted in other countries [4,6,7,[11][12][13][14][15][16][17][18][19][20]. Namely, medical students were less open towards IPE, while nursing, pharmacy, and physiotherapy students demonstrated greater readiness for IPE.…”
Section: Discussionsupporting
confidence: 88%
“…Similar results were obtained in previous studies as well [4][5][6][7][8][9][11][12][13][14][15][16][17][18]. Accordingly, there were differences among students' attitudes based on their study profile both in our study and studies conducted in other countries [4,6,7,[11][12][13][14][15][16][17][18][19][20]. Namely, medical students were less open towards IPE, while nursing, pharmacy, and physiotherapy students demonstrated greater readiness for IPE.…”
Section: Discussionsupporting
confidence: 88%
“…Similar to the findings of a recent study, our study showed that approximately half of the participants were unsure about their professional role and only a third of them disagreed with the idea that nurses and pharmacists are there to support physicians. 20 These findings might be due to the high percentage of preclinical students among the participants in our study which may reflect their lack of clinical experience. Wilby et al 21 , reported that nutrition and pharmacy students became more mindful of their professional roles in the third and fourth years of their study.…”
Section: Discussionmentioning
confidence: 87%
“…Support is also available from studies done with medical students appreciating shared learning and teamwork to provide patients with high-quality patient care [ 13 , 14 ]. In addition, a study conducted with Medical and Dental students in Princess Nourah bint Abdulrahman University, reported that students are aware that collaboration with other specialties will improve their service to patients and the community [ 15 ]. Regarding the professional identity subscale, all students agreed with the statements “Shared learning before qualification will help me become a better team worker.” “Shared learning will help to clarify the nature of patient problems” and “Shared learning with other healthcare students will help me to communicate better with patients and other professionals.” These statements correlate with a good understanding of teamwork and a positive conviction of shared learning.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the professional identity subscale, all students agreed with the statements “Shared learning before qualification will help me become a better team worker.” “Shared learning will help to clarify the nature of patient problems” and “Shared learning with other healthcare students will help me to communicate better with patients and other professionals.” These statements correlate with a good understanding of teamwork and a positive conviction of shared learning. As all the participants in the current study were from the same college, studying together in the pre-professional years according to the university policies, their professional identity increased from the first year of study [ 15 ]. However, the highest-ranking statement was “The function of nurses and therapists is mainly to provide support for doctors” in the role and responsibility with other applied medical sciences specialties.…”
Section: Discussionmentioning
confidence: 99%